Index of brief reviews in exercise physiology
Zusammenstellung von Kurzdarstellungen zu ausgewählten Themen der Sportphysiologie: Does Muscle Structure Determine Function? How Passive Structures Influence the Active Properties of Muscle Why are There Different Fibre Types? Fibre Type Distribution in Human Muscles What are the "Neural Mechanisms" of Strength Adaptations? Structural Determinants of Muscle Strength (Form and Function) Should Muscle Power be the Measure of Strength? Can Muscle Balance Really be Assessed? What are the Necessary Conditions for Muscle Hypertrophy? Training Strength, Power and Endurance using Isoinertial (Free Weights) Training What is Muscle Endurance? Is Fatigue a Necessary Prerequisite for Adaptation to a Strength Training Program? Prevention of DOMS and the Amelioration of DOMS Muscle Stiffness- is it Neurological or Mechanical? Predictors of Cardiorespiratory Capabilities Differences in Cardiorespiratory Responses to Upper and Lower Extremity Exercise Blood Pressure Responses to Intermittent and Sustained Muscle Actions Limitations to VO2 max Lactate Production and Removal During Exercise and Recovery Assessment and Detection of the Anaerobic Threshold The Influence of Exercising at the Lactate Threshold on the Aerobic Training Response How to Taper for Competition Exercising in the Heat Exercising at Altitude